International scientific conference "Сontemporary art in the digital media / mass media" - A. M. Tormakhova, (Ukrainian Cultural Studies, 2018)
From May 14 to 21, 2018, the international scientific conference "Contemporary Art in the Age of Digital Media / Mass Media" was held in the city of Karlov (Poland).